An Uncommon Clinical Presentation of a Rare Disease-Alkaptonuria: Case Report - Qureshi, Umar Abdul Ali; Malik, Naveed Akhtar (Pakistan Armed Forces Medical Journal, 2023)
Palmoplantar pigmentation is a rare clinical presentation of alkaptonuria, a rare inborn error of phenylalanine and tyrosine metabolism. Alkaptonuria occurs owing to a deficiency of an enzyme homogentisic acid oxidase inherited as an autosomal recessive disorder. We report a case of alkaptonuria, which presented with palmoplantar pigment pigmentary nail changes and the involvement of the spine and joints. He was advised of ascorbic acid along with symptomatic management and detailed counselling.